Comments on “Reflections on the Inclusion of Direct-Care Physicians as Educators in Community Hospitals” - ALEXANDRE SLULLITEL (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT We discuss the arguments exposed in the Letter to the Editor “Reflections on the Inclusion of Direct-Care Physicians as Educators in Community Hospitals”, exploring the teaching competencies necessary for community preceptors in the context of medical education, highlighting the growing responsibility of these professionals in the training of future physicians in health-deprived regions. From a narrative review, we analyze faculty development (FD) programs, emphasizing their importance in improving teaching skills, creating support networks, and providing personalized content for specific challenges. Among the competence domains identified are teaching skills, evaluation criteria, professionalism, communication, and leadership/management. In addition, we suggest Entrustable Professional Activities (EPA) as tools to assess and develop these competencies. FD programs, when well structured, benefit preceptors, students, and communities, improving the quality of teaching and care outcomes.